Polymorphism of fur coloration intensity in mammals - Yulia Zizda (Праці Теріологічної школи, 2016)
The concept of coloration polymorphism and melanism in mammals was reviewed. It was shown that polymorphism has different types and mammals color differentiation is only one of its kinds. Three classic hypotheses on the function of coloration in mammals are known: concealment, communication, and regulation of physiological processes. The attention was focused on the mammals’ coat coloration intensity and presence of black forms among mammals, including red squirrels (Sciurus vulgaris) for further exploration and analysis of causes of the fur coloration variability in the latter. The character of spots in mammals are reviewed only in a few examples. The dark phase of squirrels, which are common in the mountains, retains the heat better, and the black fur protects their skin from ultraviolet radiation, and provides better thermoregulation under damp mountain conditions. The gradual change in the red squirrel’s coat coloration, and the presence and distribution of its dark phase in mountains are associated with the feature of distribution and apparently are obeyed to Gloger’s rule.